1986
DOI: 10.1152/jappl.1986.60.4.1190
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of homeothermy in the immature rat: metabolic and thermal responses

Abstract: Steady-state thermoregulatory responses were measured in the immature rat at 5, 7, 9, 11, 13, 15, 17, and 19 days of age. Tests were conducted at controlled ambient temperatures (Ta) ranging from 22.5 to 37.0 degrees C. Colonic (Tco) and skin (tail, interscapular, abdominal) temperatures were measured, as was O2 consumption from which metabolic rate (M) was calculated. Significant improvements in homeothermic ability occurred from 5 to 19 days of age. Although the resting level of M (RMR) increased by 6.9 W/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 0 publications
3
71
0
Order By: Relevance
“…Interscapular probes were preferred over rectal probes, which are poorly tolerated in newborn mice during prolonged recordings (36 min). Previous studies in newborn rats showed that colonic and interscapular temperatures were closely correlated over TAs ranging from 22°C to 37°C (43). Each pup was placed in a restraining device in the plethysmograph to ensure that the temperature probe position remained unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…Interscapular probes were preferred over rectal probes, which are poorly tolerated in newborn mice during prolonged recordings (36 min). Previous studies in newborn rats showed that colonic and interscapular temperatures were closely correlated over TAs ranging from 22°C to 37°C (43). Each pup was placed in a restraining device in the plethysmograph to ensure that the temperature probe position remained unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…This provides an ambient temperature in which isolated animals can maintain a stable body temperature for many hours (33). Infant rats treated with LPS at this temperature did not develop the hypothermia observed with the same dose of LPS at 22…”
Section: Fever Inductionmentioning
confidence: 98%
“…Then the pup was placed in the plethysmograph in a restraining device to ensure that temperature probe position remained unchanged. Previous studies in newborn rats showed that colonic and interscapular temperatures were closely correlated over temperatures ranging from 22.5 to 37°C (38). Because the restraining device disrupted breathing measurements in several pups, we did not analyze the respiratory data.…”
Section: Animalsmentioning
confidence: 99%